Ratio Decidendi terhadap Perbuatan Aktif dan Pasif dalam Tindak Pidana Pencucian Uang Ditinjau dari Perspektif Keadilan: Analisis Putusan Nomor 816/Pid.Sus/2020/PN Bpp jo. Putusan Nomor 124/Pid/2021/PT SMR jo. Putusan Nomor 5102 K/Pid.Sus/2021 - Frisca Regina Ferreira Lay; Aksi Sinurat; Simplexius Asa (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2026)
This study examines the accuracy of the ratio decidendi in distinguishing active and passive money laundering in District Court Decision Number 816/Pid.Sus/2020/PN Bpp, High Court Decision Number 124/Pid/2021/PT SMR, and Supreme Court Decision Number 5102 K/Pid.Sus/2021. This normative legal research applies statutory, conceptual, and case approaches. Primary legal materials comprise relevant legislation and court decisions, while secondary materials include legal literature and previous studies. The materials were analyzed qualitatively using descriptive and prescriptive reasoning. The findings show that the court applied Article 5 of Law Number 8 of 2010 and sentenced the defendant to four years’ imprisonment and a fine of IDR 900 million. However, the proven facts revealed fund flows totaling IDR 56.637 billion, followed by transfers, fictitious interest payments, asset purchases, and business financing. These actions indicate characteristics of active money laundering under Articles 3 and 4. The court’s reasoning did not adequately compare the three alternative charges or comprehensively assess the defendant’s intent and transactional control. Accurate offense classification is therefore essential to ensure consistent legal reasoning, proportional criminal responsibility, fairness, and effective prevention of money laundering.